2019
DOI: 10.1016/j.neuron.2019.03.044
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Dependent Secretion of Synaptic Organizer Cbln1 from Lysosomes in Granule Cell Axons

Abstract: Synapse formation is achieved by various synaptic organizers. Although this process is highly regulated by neuronal activity, the underlying molecular mechanisms remain largely unclear. Here we show that Cbln1, a synaptic organizer of the C1q family, is released from lysosomes in axons but not dendrites of cerebellar granule cells in an activity-and Ca 2+dependent manner. Exocytosed Cbln1 was retained on axonal surfaces by binding to its presynaptic receptor neurexin. Cbln1 further diffused laterally along the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 61 publications
(80 reference statements)
1
45
0
Order By: Relevance
“…In this latter regard, lysosome exocytosis was previously shown to promote axon outgrowth in rat corticostriatal neurons ( Martinez-Arca et al, 2001 ). Moreover, a recent study showed that the synaptic organizer Cbln1 is exocytosed from axonal lysosomes into the axon terminal for activity-dependent synapse modification in cerebellar granular cells ( Ibata et al, 2019 ). Finally, lysosomal function is required for the clearance of damaged proteins or organelles in the axon, thus contributing to the maintenance of synaptic function ( Boecker and Holzbaur, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this latter regard, lysosome exocytosis was previously shown to promote axon outgrowth in rat corticostriatal neurons ( Martinez-Arca et al, 2001 ). Moreover, a recent study showed that the synaptic organizer Cbln1 is exocytosed from axonal lysosomes into the axon terminal for activity-dependent synapse modification in cerebellar granular cells ( Ibata et al, 2019 ). Finally, lysosomal function is required for the clearance of damaged proteins or organelles in the axon, thus contributing to the maintenance of synaptic function ( Boecker and Holzbaur, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the disease process of SCA2, it is unclear at present what the crucial mRNA targets of such splice anomalies can be. Neurexin-1 ( Nrxn1 ) splicing is under the control of Sam68, its role as presynaptic receptor for the Neuroligins ( Nlgn1-3) and the Cerebellins ( Cbln1-4) , with subsequent effects on postsynaptic GluD2 and Adam23 [ 88 , 89 ], may be responsible for the downregulation of these factors, and all these anomalies together suggest that synaptic adhesion is impaired. Of course, the Camk2a mRNA itself can also be alternatively spliced, and numerous other excitability factors in neural tissue are regulated in dependence on trophic stimuli versus stress, via alternative splicing or by alternative polyadenylation, so extensive studies at genome-wide levels will be necessary to obtain a systematic overview.…”
Section: Discussionmentioning
confidence: 99%
“…Wound repair is fast and critically dependent on the influx of extracellular Ca 2+ , which triggers a sequence of steps culminating in the restoration of PM integrity ( Andrews and Corrotte, 2018 ). Among the better defined roles of Ca 2+ influx through PM wounds are the recruitment of annexins ( Swaggart et al, 2014 ), activation of the muscle-specific Ca 2+ -binding protein dysferlin ( Bansal et al, 2003 ) and exocytosis of lysosomes at sites of PM injury ( Cheng et al, 2014 ; Forestier et al, 2011 ; Ibata et al, 2019 ; Luisoni et al, 2015 ; Reddy et al, 2001 ). Ca 2+ -dependent exocytosis was initially proposed to be sufficient to promote cell resealing, by patching the wound ( Terasaki et al, 1997 ) or reducing PM tension ( Togo et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%